If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -1(4x + 5) = 7x + -23 Reorder the terms: 8x + -1(5 + 4x) = 7x + -23 8x + (5 * -1 + 4x * -1) = 7x + -23 8x + (-5 + -4x) = 7x + -23 Reorder the terms: -5 + 8x + -4x = 7x + -23 Combine like terms: 8x + -4x = 4x -5 + 4x = 7x + -23 Reorder the terms: -5 + 4x = -23 + 7x Solving -5 + 4x = -23 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -5 + 4x + -7x = -23 + 7x + -7x Combine like terms: 4x + -7x = -3x -5 + -3x = -23 + 7x + -7x Combine like terms: 7x + -7x = 0 -5 + -3x = -23 + 0 -5 + -3x = -23 Add '5' to each side of the equation. -5 + 5 + -3x = -23 + 5 Combine like terms: -5 + 5 = 0 0 + -3x = -23 + 5 -3x = -23 + 5 Combine like terms: -23 + 5 = -18 -3x = -18 Divide each side by '-3'. x = 6 Simplifying x = 6
| -3-7(5+5X)=-178 | | 3=3-8r+2r | | D/18=20/9 | | 2(2-3x)=3(2x+5) | | 3(2n+5)=7(4n+3)+3 | | 2x-7=5+5X | | x-7+4=-5 | | D=100/0,2 | | D=500/0,2 | | 3x+12+x+25+3x-27=360 | | 2*-y=6 | | p=t+cm*c | | -3x+15=45 | | 3(4x-1)=13 | | 2/3m=18 | | 15/x-4=9/x | | 4*-12y=120 | | 15+3x=24+6x | | log(8*x^2)(-4x^3)=log(8*x^2)(8*x^2) | | 3x^5-5x^3+2=0 | | log(8*x^2)(-4x^3)=8*x^2 | | 3x-17=2(-4x+4) | | 2(3x+5)=x+15 | | 5a+9a=6 | | y=in(6x) | | 0.5x+0.4(20)=0.3(x+20) | | -7x^2+10+x^4=0 | | 7w-19w=60 | | 9/21=15/b | | 67-(34d+2)=8(d-2)7 | | 3w-19x=32 | | 4(8-x)+18=10 |